2022
DOI: 10.1186/s13014-022-02131-1
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo γH2AX assay for tumor radiosensitivity in primary prostate cancer patients and correlation with clinical parameters

Abstract: Backround Accurate surrogate parameters for radio resistance are warranted for individualized radiotherapy (RT) concepts in prostate cancer (PCa). The purpose of this study was to assess intertumoral heterogeneity in terms of radio resistance using an ex-vivo γH2AX assay after irradiation of prostate biopsy cores and to investigate its correlation with clinical features of respective patients as well as imaging and genomic features of tumor areas. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…γH2AX has been widely used to determine DNA damage and repair kinetics [ 84 ]. Moreover, preclinical and clinical studies have revealed that it can be used to image DNA damage and therapy response after radiation or radioligand therapy [ 85 , 86 ]. To assess the repair capacity of each tumour and its response, he discussed the possibility of monitoring the DNA damage response caused by 177 Lu-PSMA-617.…”
Section: Introductionmentioning
confidence: 99%
“…γH2AX has been widely used to determine DNA damage and repair kinetics [ 84 ]. Moreover, preclinical and clinical studies have revealed that it can be used to image DNA damage and therapy response after radiation or radioligand therapy [ 85 , 86 ]. To assess the repair capacity of each tumour and its response, he discussed the possibility of monitoring the DNA damage response caused by 177 Lu-PSMA-617.…”
Section: Introductionmentioning
confidence: 99%